The causes of word borrowings in languages (Journal of Science-Innovative Research in Uzbekistan, 2023)
This article is about the placement of a newly introduced word,  its ability to convey the basic needs of the people hearing it, and the internal  capabilities of the coordinating language. We analyzed about determining whether  it changes completely or is only used once before disappearing